Factors influencing accounting research output in South Africa's universities of technology - Mzwandile Mbambo; Odunayo Olarewaju; Thabiso Sthembiso Msomi (Cogent Business & Management, 2022)
This study examines factors influencing accounting research output in universities of technology (UoTs) in South Africa by employing descriptive statistics. The study applied a quantitative research method and primary data was used to compile information. The data was collected by using a 4 Likert scale closed-ended questionnaire. The questionnaire was administered to one hundred accounting academics across the six UoTs in South Africa. Descriptive and inferential statistics such as multivariate regression was used to analyse the data. The findings show that research funding (t~=~3.125, p <~0.002, Ø~=~0.277) and research policies (t~=~4.740, p <~0.000, Ø~=~0 .453) positively and significantly affect research output while the enabling environment was negative and insignificant (t~=~−0.613, p >~0.5, Ø~=~−0.055). Based on the inverse effect of the enabling environment on accounting research output, it was recommended that the environment influencing research activities needs to be strengthened to promote research culture among accounting academics in UoTs. More so, more institutional support for research is needed such as allocating research grants/funds to academic staff and managing workload to give room to research activities.
Keywords: 650; academics; accounting; research output; South Africa; universities of technology